“Nondetected”: The Politics of Measurement of Asbestos in Talc, 1971–1976 - Rosner, David (Am J Public Health, 2019)
The recent lawsuits against Johnson & Johnson have raised the issue of what and when talcum powder manufacturers knew about the presence of asbestos in their products and what they did or did not do to protect the public. Low-level exposure to asbestos in talc is said to result in either mesothelioma or ovarian cancer. Johnson & Johnson has claimed that there was “no detectable asbestos” in their products and that any possible incidental presence was too small to act as a carcinogen. But what exactly does “nondetected” mean? Here, we examine the historical development of the argument that asbestos in talcum powder was “nondetected.” We use a unique set of historical documents from the early 1970s, when low-level pollution of talc with asbestos consumed the cosmetics industry. We trace the debate over the Food and Drug Administration’s efforts to guarantee that talc was up to 99.99% free of chrysotile and 99.9% free of amphibole asbestos. Cosmetic talc powder manufacturers, through their trade association, pressed for a less stringent methodology and adopted the term “nondetected” rather than “asbestos-free” as a term of art.